Hubungan antara rasio neutrofil limfosit dengan derajat klinis COVID-19 pada pasien anak di RSUD Tarakan provinsi Kalimantan Utara - Daniel kurniawan Sintoro; Franky Sientoro; Dian Artanti (DiscoverSys Inc., 2021)
Introduction: Coronavirus Disease-19 (COVID-19) is an outbreak that spread in early 2020 caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), this disease has a wide spectrum of symptoms from asymptomatic to severe respiratory symptoms. Neutrophil-lymphocyte ratio (NLR) is widely used as a marker of inflammation against viral infections, including SARS-CoV-2. This study was conducted to determine the relationship between NLR and the clinical degree of COVID-19 in pediatric patients at the Tarakan General Hospital in North Kalimantan Province.Methods: A cross-sectional study was conducted on pediatric patients with COVID-19 infection who were treated in the COVID-19 isolation room at Tarakan Hospital, North Kalimantan for the period March 2020 – February 2021. There were 32 children who met the inclusion and exclusion criteria. Data on age, sex, body weight, neutrophil and lymphocyte counts, as well as the clinical degree of COVID-19 were collected from medical records. The NLR data was then categorized to NLR >3.13 or NLR <3.13 and searched for the relationship with the clinical degree of COVID-19. Spearman correlation test was used for bivariate analysis.Results: The clinical degree of mild COVID-19 was found in 21 children (65.62%). NLR values in mild clinical grade were mostly increased (46.87%) than than which did not increase (21.87%). All children with moderate clinical COVID-19 infection had RNL > 3.13 (18.74%). In asymptomatic infection, no children having an increase in RNL (12.5%). The Spearman correlation test between NLR and the clinical degree of COVID-19 resulted in a correlation coefficient (r) = 0.758 (p < 0.001).Conclusion: There is a strong relationship between the Neutrophil-Lymphocyte ratio and the clinical degree of COVID-19 in pediatric patients at Tarakan Hospital, North Kalimantan Province. Pendahuluan: Coronavirus Disease-19 (COVID-19) adalah wabah yang menyebar pada awal 2020 disebabkan oleh virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), penyakit ini memiliki spektrum gejala yang luas dari asimptomatis hingga gejala respiratori yang berat. Rasio neutrofil-limfosit (RNL) banyak digunakan sebagai penanda inflamasi terhadap infeksi virus, termasuk SARS-CoV-2. Penelitian ini dilakukan untuk mengetahui besar hubungan antara RNL dengan derajat klinis COVID-19 pada pasien anak di Rumah Sakit Umum Daerah (RSUD) Tarakan Provinsi Kalimantan Utara.Metode: Studi potong lintang dilakukan pada pasien anak dengan infeksi COVID-19 yang dirawat di ruang isolasi COVID-19 RSUD Tarakan Kalimantan Utara periode Maret 2020 – Febuari 2021. Terdapat 32 anak yang memenuhi kriteria inklusi dan eksklusi. Data mengenai usia, jenis kelamin, berat badan, jumlah hitung neutrofil dan limfosit, serta derajat klinis COVID-19 dikumpulkan dari rekam medis. Data RNL kemudian dikategorikan berdasarkan adanya peningkatan >3,13 atau tidak adanya peningkatan <3,13 dan dicari hubungan dengan derajat klinis COVID-19. Uji korelasi Spearman digunakan untuk analisis bivariat.Hasil: Derajat klinis COVID-19 ringan ditemukan pada 21 anak (65,62%). Nilai RNL pada derajat klinis ringan sebagian besar meningkat (46,87%) daripada pada derajat klinis ringan dengan RNL yang tidak meningkat (21,87%). Semua anak yang mengalami infeksi COVID-19 dengan derajat klinis sedang memiliki RNL >3,13 (18,74%). Hal ini berbanding terbalik dengan derajat klinis asimtomatik, dengan semua anak tidak mengalami peningkatan RNL (12,5%). Uji korelasi Spearman antara RNL dengan derajat klinis COVID-19 menghasilkan koefisien korelasi (r) = 0,758 (p< 0,001).Kesimpulan: Terdapat hubungan kuat antara rasio Neutrofil-Limfosit dengan derajat klinis COVID-19 pada pasien anak di RSUD Tarakan Provinsi Kalimantan Utara.